Instilling the Values of Tasammuh in Fiqh Learning at Pesantren Terpadu Serambi Mekkah Students in Padangpanjang City - Natsir, Albert (BiCED Proceeding, 2024)
This study aims to describe the cultivation of tasammuh values in fiqh learning for students of Pesantren Terpadu Serambi Mekkah Padangpanjang City and the obstacles in the learning process. This type of research is a field study (field research) with qualitative research methods. While the object of this research is the students of Pesantren Terpadu Serambi at class III Ulya. The data collection method uses interviews, observation, and documentation. The results of this study indicate that the cultivation of tasammuh values in Fiqh learning at Pesantren Terpadu Serambi Mekkah in Padang Panjang City through Ikhtilaf materials in Fiqh Ibadah how it is understood and practised. The material in fiqh learning can form an attitude in children to respect each other and appreciate the differences in khilafiah problems So, what is taught in the Pesantren Terpadu Serambi Mekkah of Padang Panjang City has contained tasammuah materials in respecting differences. The obstacles in instilling the values of tasammuah in students are that there is no balance of encouragement from parents, ustadz and ustadzah and the school, limited material and examples.